Characterization of antibacterial activity and mechanisms of two linear derivatives of bactenecin. (June 2019) - Liu, Fei; Wang, Haimei; Cao, Songsong; Jiang, Chenggang; Hou, Juncai
Abstract: Antibiotic resistance is a significant global healthcare issue, and the development of alternative classes of antimicrobial agents with new modes of action is therefore critical. In the current study, two derivatives of the antimicrobial peptide bactenecin which were Bac2a, a 12-residue peptide, and Bac8c, an 8-residue peptide were synthesized, then their antimicrobial properties, stabilities, and mechanisms of action were investigated. Results showed that the minimum inhibitory concentrations (MICs) of Bac2a against gram-negative and gram-positive bacteria ranged from 2 to 32 μM, while Bac8c exhibited greater antimicrobial activity with MICs ranging from 2 to 16 μM Bac8c also exhibited lower hemolytic and cytotoxic activities compared with those of Bac2a. The antibacterial activities of the peptides were not inhibited by heat, and Bac8c possessed a higher antibacterial activity in the presence of salts and enzymes. Fluorescence spectroscopy, flow cytometry, and scanning and transmission electron microscopy indicated that Bac8c exhibited high antimicrobial potency by inducing cytoplasmic membrane potential loss, as well as membrane permeabilization and disruption. Based on the results of the analyses, Bac8c represents a promising candidate for novel antimicrobial applications. Highlights: Two derivatives of antimicrobial peptide bactenecin which were Bac2a and Bac8c were synthesized and characterized. Bac2a and Bac8c had strong thermal stability, and Bac8c exhibited higher stability against salts and enzymes treatments. Bac8c exhibited high antimicrobial potency by inducing cell membrane potential loss, permeabilization and disruption.